EUPHEMISM AS POLITENESS STRATEGY: INVESTIGATING LANGUAGE USE AMONG CHILDREN OF INDONESIAN MIGRANT WORKERS IN MALAYSIA - Aswan, Aswan; Suyitno, Imam; Santoso, Anang; Syahri, Moch.; Amir, Asmah (ISLLAC : Journal of Intensive Studies on Language, Literature, Art, and Culture, 2023)
This study explores euphemism in the language use of Indonesian migrant workers' children in Malaysia. Focusing on intercultural communication within Indonesian schools, it employs a qualitative case study approach with observational data collection. Results reveal diverse euphemistic forms (1) one-word substitutions, (2) circumlocution, (3) borrowing, (4) abbreviation, (5) hyperbole, and (6) figurative expression in Bugisness, Indonesian, English, and Malaysian. These euphemisms serve as linguistic politeness strategies for indirect speech acts in communication.